2020
DOI: 10.1108/apjml-07-2018-0283
|View full text |Cite
|
Sign up to set email alerts
|

Seriously, conspicuous consumption? The impact of culture, materialism and religiosity on Malaysian Generation Y consumers' purchasing of foreign brands

Abstract: PurposeThe purpose of this research is to understand the importance of value orientation on conspicuous consumption in the youth market segment in Southeast Asia. In particular, the focus is to understand three different types of value orientation (specifically cultural values, material values and religious values) and its effects on conspicuous consumption behaviour.Design/methodology/approachAn integrative theoretical model is proposed based on Hofstede's cultural dimension, the materialism value scale and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 193 publications
(204 reference statements)
4
61
0
2
Order By: Relevance
“…He found a significant relationship between competitiveness and the conspicuous consumption of innovative electronic products. Other studies have found significant relationships between materialism and conspicuous consumption (Kim & Jang, 2017;Podoshen & Andrzejewski, 2012;Zakaria et al, 2020), whereby materialism is an elemental personality trait that participates in the constitution of competitiveness as a compound personality trait within Mowen's (2000) 3M model.…”
Section: Theoretical Implicationsmentioning
confidence: 92%
“…He found a significant relationship between competitiveness and the conspicuous consumption of innovative electronic products. Other studies have found significant relationships between materialism and conspicuous consumption (Kim & Jang, 2017;Podoshen & Andrzejewski, 2012;Zakaria et al, 2020), whereby materialism is an elemental personality trait that participates in the constitution of competitiveness as a compound personality trait within Mowen's (2000) 3M model.…”
Section: Theoretical Implicationsmentioning
confidence: 92%
“…Malays are generally Muslims (Alatas, 1977;Idris, 2008;Zakaria et al, 2020) and can be identified through their physical appearance, including skin color, clothing and name.…”
Section: Methodology 31 Respondentsmentioning
confidence: 99%
“…Sebagai contoh, dapat dilihat bahawa pengguna daripada latar belakang budaya yang berbeza mentafsir komunikasi secara berlainan. Penyelidikan juga telah mengemukakan fakta yang menyatakan bahawa pengguna lebih menggemari komunikasi atau produk yang sesuai dengan budaya mereka (Zakaria, Wan-Ismail & Abdul-Talib, 2020;Jianlin, 2008). Oleh sebab itu, penyelidik terus berusaha untuk mengetahui bagaimana faktor budaya mempengaruhi tingkah laku pengguna dan aktiviti pemasaran tertentu seperti pemasaran media sosial (Khan, Dongping & Wahab, 2016).…”
Section: Perbezaan Budaya Dalam Sikapunclassified